2006
DOI: 10.1111/j.1532-950x.2006.00160.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphography of the Thoracic Duct by Percutaneous Injection of Iohexol into the Popliteal Lymph Node of Dogs: Experimental Study and Clinical Application

Abstract: Percutaneous popliteal lymph node administration of iohexol should be considered as an alternative to mesenteric lymph node injection for radiographic identification of the thoracic duct in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
47
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 8 publications
(10 reference statements)
1
47
1
Order By: Relevance
“…A previous study reported that radiography with an inadequate delay time requires additional injection of iohexol into the popliteal lymph node [8]. The present study also suggests that determination of the delay time for computed tomographic scanning is necessary due to the disappearing nature of the contrast media in the thoracic duct.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…A previous study reported that radiography with an inadequate delay time requires additional injection of iohexol into the popliteal lymph node [8]. The present study also suggests that determination of the delay time for computed tomographic scanning is necessary due to the disappearing nature of the contrast media in the thoracic duct.…”
Section: Discussionmentioning
confidence: 49%
“…Naganobu et al described performance of popliteal lymphography by injection of iohexol with a volume of 5 to 10 ml and an injection time of an average of 5 min. Although we used similar methods, smaller amounts of iohexol (60 mgI/kg) were used, which facilitates a much faster injection time without a loss of image quality in lymphatic duct opacification [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, results of previous studies have been variable. For instance, Naganobu et al (2006) observed a 100% contrast uptake into the TD after an injection of 10 ml of iohexol at 300 mg/ml into the popliteal LN of healthy experimental dogs. These results suggest that the success rate of popliteal lymphangiography in dogs is higher than in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…To visualize the thoracic duct, dyes such as India ink (for anatomical purpose) and methylene blue (MB) or X-ray contrast media have been injected into the mesenteric, inguinal, popliteal, and metatarsal lymph vessels [1,3,8] or the mesenteric, popliteal, and axillary lymph nodes [5,9,12]. However, except for the popliteal lymph node, surgery is required to approach these nodes and vessels, before injections of dyes or X-ray contrast media.…”
mentioning
confidence: 99%